Time-course of tissue factor plasma level in patients with acute coronary syndrome - Bis, Josef; Vojáček, Jan; Dušek, Jan; Pecka, Miroslav; Palička, Vladimír; Malý, Jaroslav; Šťásek, Josef (Physiological research, 2009)
Enhanced expression of tissue factor (TF) may result in thrombosis contributing to acute clinical consequences of coronary artery disease. Several studies demonstrated elevated plasma levels of TF in patients with acute coronary syndrome (ACS). The aim of our study was to compare the concentrations of TF in coronary sinus (CS), proximal part of the left coronary artery (LCA) and peripheral vein (PV) of patients with ACS and stable coronary artery disease (SCAD). Time course of the TF plasma levels in PV was followed on day 1 and day 7 after index event of ACS presentation and was compared to day 0 values. No heparin was given prior to the blood sampling. Twenty-nine patients in the ACS group (age 63.6±10.8 years, 20 males, 9 females) and 24 patients with SCAD (age 62.3±8.1 years, 21 males, 3 females) were examined. TF plasma level was significantly higher in patients with ACS than in those with SCAD (239.0±99.3 ng/ml vs. 164.3±114.2 ng/ml; p=0.016). There was no difference in TF plasma levels in PV, CS and LCA (239.0± 99.3 ng/ml vs. 253.7±131.5 ng/ml vs. 250.6±116.4 ng/ml, respectively). TF plasma levels tended to decrease only nonsignificantly on the day 7 (224.4±109.8 ng/ml). Significant linear correlation between TF and high sensitivity CRP (hs-CRP) levels on day 0 was found. In conclusion, TF plasma levels are elevated in patients with ACS not only locally in CS but also in systematic circulation. Our data support the relationship between TF production and proinflammatory mediators.
Keywords: financování organizované; Acute Coronary Syndrome; Female; Thromboplastin; ženské pohlaví; Coronary Sinus; lidé; tkáňový faktor; Financing, Organized; nemoci koronárních tepen; Male; Aged; Coronary Artery Disease; koronární sinus; lidé středního věku; senioři; akutní koronární syndrom; mužské pohlaví; Middle Aged; Humans